African peacekeeping - Fisher, Jonathan 1985-; Wilén, Nina 1978- (Cambridge University Press, 2022)
Exploring the story of Africa's contemporary history and politics through the lens of peacekeeping, this concise and accessible book, based on over a decade of research across ten countries, focuses not on peacekeeping in Africa but, rather, peacekeeping by Africans. Going beyond the question of why post-conflict states contribute troops to peacekeeping efforts, Jonathan Fisher and Nina Wilén demonstrate how peacekeeping is - and has been - weaved into Africa's national, regional and international politics more broadly, as well as what implications this has for how we should understand the continent, its history and its politics. In doing so, and drawing on fieldwork undertaken in every region of the continent, Fisher and Wilén explain how profoundly this involvement in peacekeeping has shaped contemporary Africa
Title from publisher's bibliographic system (viewed on 13 Jan 2022)
Introduction -- The (Pre-) History and Evolution of African Peacekeeping -- New Means of Staying in Power: Regime Maintenance through Peacekeeping -- From the Local to the Global: The Connection Between the Domestic and the International -- Constructing a New Identity as a Peacekeeper -- From Peacekept to Peacekeeper: Post-Conflict Peacekeeping -- What is "African" About African Peacekeeping? -- Conclusion
Keywords: Peacekeeping forces / Africa; Conflict management / Africa; National security / Africa; Friedenssicherung; Internationale Organisation; Afrika